Electron Transfer Rates in Solution: Toward a Predictive First Principle Approach - Anna Leo; Francesco Ambrosio; Alessandro Landi; Andrea Peluso (Chemistry, 2023)
Using a very recently proposed theoretical model, electron transfer rates in solution are calculated from first principles for different donor-acceptor pairs in tetrahydrofuran. We show that this approach, which integrates tunneling effects into a classical treatment of solvent motion, is able to provide reliable rate constants and their temperature dependence, even in the case of highly exergonic reactions, where Marcus’ theory usually fails.